THE EFFECT OF BLENDED LEARNING ON STUDENT LEARNING OUTCOMES IN MULTIMEDIA LEARNING IN HIGHER EDUCATION - Zulkifli Zulkifli; Andi Putra (International Journal Labs, 2022)
Learning is a basic need for everyone in meeting educational needs in the educational hierarchy. However, in the learning process itself, there are often various kinds of obstacles in the learning process. In learning multimedia courses at STT Payakumbuh, the problem is that the achievement of student learning outcomes is still low, to overcome these problems, a blended learning model is used so that the achievement of multimedia learning can increase. and to determine effect of applying blended learning in multimedia learning, a quasi-experimental study was conducted with purposive nonequivalent control groups, The research was conducted at Sekolah Tinggi Teknologi Payakumbuh (STT Payakumbuh) in the Multimedia course with a sample class of class 2017 as an experimental group using blended learning and class 2018 as a control class using traditional learning in the classroom. The study was conducted for 7 sessions with data collection techniques in the form of multiple-choice tests consisting of pretest and posttest. After that, the calculations were carried out using the t-test in both classes and obtained a value of 0.000 or sig < 0.05 (5%), then it can be interpreted that H0 is rejected and H1 is accepted. So this study shows that there is an effect of blended learning on student learning outcomes in multimedia courses at STT Payakumbuh.